Enzymes in the Valorization of Waste : Enzymatic Hydrolysis of Waste for Development of Value-added Products - Verma, Pradeep, editor 650118 (Boca Raton : CRC Press, 2023)
Enzymes play a vital role in the enzymatic hydrolysis of waste for its conversion to useful value-added products. Enzymatic Hydrolysis of Waste for Development of Value-added Products focusses on the role of key enzymes such as cellulase, hemicellulases, amylases, and auxiliary enzymes (LMPOs), used in the hydrolysis step of the biorefinery setup. Further, it discusses the role of enzymes in the generation of reducing sugars and value-added compounds, with major emphasis on recent advances in the field. The mechanism, importance, type, evolution, and role of enzymes in hydrolysis constitute the crux of this volume, which is illustrated with examples and pertinent case studies.